2005
DOI: 10.1261/rna.7135305
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the deadenylase activity of proteins of the Caf1 family in human

Abstract: The yeast Pop2 protein, belonging to the eukaryotic Caf1 family, is required for mRNA deadenylation in vivo. It also catalyzes poly(A) degradation in vitro, even though this property has been questioned. Caf1 proteins are related to RNase D, a feature supported by the recently published structure of Pop2. Yeast Pop2 contains, however, a divergent active site while its human homologs harbor consensus catalytic residues. Given these differences, we tested whether its deadenylase activity is conserved in the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 34 publications
4
81
0
2
Order By: Relevance
“…CCF-1 possesses a DEDD-type, magnesium-dependent exoribonuclease domain and shares significant sequence identity with other Pop2p orthologs ( Figure 3, A and B). Mammalian Pop2 is an enzymatically active deadenylase (Thore et al 2003;Viswanathan et al 2004;Bianchin et al 2005). Since CCF-1 contains all active site residues ( Figure 3A), it too is likely an active deadenylase.…”
Section: Fbf-1 Co-immunoprecipitates With Gld-1 Mrnamentioning
confidence: 99%
“…CCF-1 possesses a DEDD-type, magnesium-dependent exoribonuclease domain and shares significant sequence identity with other Pop2p orthologs ( Figure 3, A and B). Mammalian Pop2 is an enzymatically active deadenylase (Thore et al 2003;Viswanathan et al 2004;Bianchin et al 2005). Since CCF-1 contains all active site residues ( Figure 3A), it too is likely an active deadenylase.…”
Section: Fbf-1 Co-immunoprecipitates With Gld-1 Mrnamentioning
confidence: 99%
“…While much less is known about the RNA turnover processes in S. pombe, the strong conservation of the caf1 gene and the Ccr4-Not complex in eukaryotes from yeast to humans led us to suggest that Pop2p maintains a similar function in S. pombe as has been observed in other eukaryotes (Albert et al 2000;Bianchin et al 2005). Most importantly, the S. pombe ortholog has a fully conserved DEDDh active site, and combined structural and functional data subsequently showed that the protein is a functional 39-59 exonuclease specific to RNA with a tuneable preference for poly-A sequences (Jonstrup et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…The two CAF1 proteins seem to be integrated into the CCR4-NOT complex in a mutually exclusive manner, and the same is true for the two CCR4 proteins (Lau et al 2009). All four proteins are active as deadenylases in vitro (Viswanathan et al 2003Bianchin et al 2005;Morita et al 2007). They play overlapping roles in mRNA deadenylation, and their catalytic activities are essential for their in vivo functions, as shown by dominant-negative effects of mutant variants (Yamashita et al 2005;Morita et al 2007;Mauxion et al 2008;Schwede et al 2008;Zheng et al 2008;Aslam et al 2009).…”
Section: Introductionmentioning
confidence: 99%